Aplikasi Citicoline dalam Pengobatan Stroke Hemoragik: Laporan Kasus Berbasis Bukti - endyjulianto; jekson martiar siahaan; kenvin rusli; Putri Chairani Eyanoer (PT Kalbe Farma Tbk., 2024)
Background: Choline-containing phospholipids, citicoline, and choline alphoscerate have been proposed as adjuvants in acute stroke treatment. An evidence-based case report (EBCR) was conducted to examine the benefits of citicoline in hemorrhagic stroke (SH) patients. Method: Search for articles published from October 2019-2023 from PubMed, Cochrane, Google Scholar, and ProQuest sources using the keywords “Citicoline”, “Hemorrhagic Stroke”, “Choline”, and “Intracerebral Hemorrhage”. The search results were evaluated using inclusion and exclusion criteria. Selected full-text studies were evaluated. The final selection results were critically reviewed based on validity, importance, and applicability by the three authors. Results: One study was considered valid, important, and applicable. The quality of this study is very high based on the literature review. Conclusion: The study shows that citicoline has the potential as an adjuvant therapy to improve clinical outcomes in SH patients, although it does not sufficiently improve neurological or functional outcomes.